2017
DOI: 10.1080/17454832.2017.1403458
|View full text |Cite
|
Sign up to set email alerts
|

Development of an art-therapy intervention for patients with personality disorders: an intervention mapping study

Abstract: Art therapy for people diagnosed with personality disorders (PD) cluster B/C seems valuable to explore dysfunctional patterns in managing emotions. Current art therapy interventions are based on practical beliefs or commonsense approaches, without a sound basis in research results. To increase the effectiveness of art therapy for this target group, a planned, systematic and theory-based approach is needed. The principles of Intervention Mapping were applied to guide the development, implementation, and planned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…This fits the core problems of people with PD such as managing emotions and having lower emotional awareness (Levine, Marziali, & Hood, 1997;Linehan & Heard, 1992;Westen, 1991). Art therapy is developed as a 'bottom-up' strategy for emotion regulation, starting with experiences using mental images, and then aimed at behaviour change and resulting insight (Haeyen, van Hooren, et al, 2017;Horn et al, 2015). In contrast, verbal therapy is considered a 'top-down' strategy, starting with cognitions to manage emotional experiences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This fits the core problems of people with PD such as managing emotions and having lower emotional awareness (Levine, Marziali, & Hood, 1997;Linehan & Heard, 1992;Westen, 1991). Art therapy is developed as a 'bottom-up' strategy for emotion regulation, starting with experiences using mental images, and then aimed at behaviour change and resulting insight (Haeyen, van Hooren, et al, 2017;Horn et al, 2015). In contrast, verbal therapy is considered a 'top-down' strategy, starting with cognitions to manage emotional experiences.…”
mentioning
confidence: 99%
“…The results of a recent randomised controlled trial (RCT) by Haeyen, van Hooren, et al (2017) showed that art therapy is an effective treatment for PD patients because it not only reduces PD pathology (e.g. emotion dysregulation) and maladaptive Figure 1.…”
mentioning
confidence: 99%
“…Self‐expression concerns the authentic expression of one's own personality and feelings, in painting, poetry or other creative activity . Art therapy for PD patients is focused on discovering, improvising and intuitively acting during the art process, envisaging the own artwork as self‐product and active reflection on the art process and product . The analogy between the art process and product with functioning in daily life can be examined, and a mindful self‐dialogue can be stimulated by self‐expression in art .…”
Section: Discussionmentioning
confidence: 99%
“…39 Art therapy for PD patients is focused on discovering, improvising and intuitively acting during the art process, envisaging the own artwork as self-product and active reflection on the art process and product. 40,41 The analogy between the art process and product with functioning in daily life can be examined, 42 and a mindful self-dialogue can be stimulated by self-expression in art. 43,44 Emotion regulation implies the recognition and acceptance of emotions, problem solving and reappraisal, which appear to be protective against psychopathology (opposite of dysregulation: suppression, avoidance and rumination).…”
Section: Discussionmentioning
confidence: 99%
“…Here the clients were found to mentalize emotions better after partaking in AT. Haeyen et al, (2017) found very large effect sizes in reduced personality disorder pathology and the development of adaptive modes, self-regulation, and mentalization in their RCT involving short-term AT in a group setting with patients with personality disorders cluster B and C. Haeyen (2018) found AT to be an effective treatment in itself and recommended health care to invest in more AT for patients with personality disorders. A study from the USA showed that both women and men in prison reported reduced depression and increased experience of internal control (locus of control) after 15 weeks of group therapy with AT (Gussak, 2009).…”
mentioning
confidence: 99%